Qibla Direction of the Historical Mosque in Pekalongan City: Accuracy and Tolerance - 'Alamul Yaqin; Iqbal Kamalludin (Universitas Islam Negeri Mataram, 2024)
The problem of the Qibla direction of the mosque is still one of the things that often occurs in society. In the modern era that has been equipped with sophisticated tools in determining the Qibla direction, there are still mosques and musala that are not facing the Qibla, moreover mosques that are hundreds of years old with traditional equipment. Pekalongan has three historical mosques: Aulia Sapuro Mosque, Jami' Mosque of Pekalongan City and Wakaf Mosque, which was the beginning of the spread of Islam in Pekalongan. This article aims to find out the history of the oldest mosque in Pekalongan and determine the accuracy and tolerance of its Qibla direction. This research is a qualitative research and data collection uses the field through interviews and observations. The data analysis technique uses comparative descriptive. The results of this article are as follows: The determination of the Qibla direction by 3 methods (Compass, Compass and magnetic declination, Local Ra?du Qiblah) shows the largest inclination in the Qibla direction of the Aulia Sapuro Mosque used the Local Ra?du Qiblah method and the smallest inclination in the Qibla direction of the Wakaf Mosque used the compass method. The inclination of the Qibla direction of the 3 mosques is still included in the category of Qibla direction tolerance, so it is valid to pray in the mosque.